Pengaruh Kebijakan Manajemen terhadap Kinerja Bank Syariah - Meilina, Indah; Wiranata, Angga; Chairina, Chairina (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to help Islamic bank management see their overall performance so far. The level of overall performance referred to is not only financial performance as measured by the best profitability analyzing the rate of return on profits, but also measured through the Islamic maqashid index (MSI), which is a measurement of overall performance in accordance with the initial performance. motive for the establishment of Islamic banks. thus the management of financial institutions will have rules relating to modern operations so that Islamic banks are in a condition that can comply with Islamic rules. The approach used is through quantitative research by looking for data according to statistics. The consequences of this study show the effect of control coverage on the performance of Islamic banks as a whole.